Share Buy-Backs in Germany Overreaction to Weak Signals? - Andreas Hackethal; Alexandre Zdantchouk (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
This paper investigates the magnitude and the main determinants of share price reactions to buy-back announcements of German corporations. For our comprehensive sample of 224 announcements that took place between May 1998 and April 2003 we find average cumulative abnormal returns around -7.5% for the thirty days preceding the announcement and around +7.0 % for the ten days following the announcement. We regress post-announcement abnormal returns with multiple firm characteristics and provide evidence which supports the undervaluation signaling hypothesis but not the excess cash hypothesis or the tax-efficiency hypothesis. In extending prior empirical work, we also analyze price effects from initial statements of firms that they intend to seek shareholder approval for a buy-back plan. Observed cumulative abnormal returns on this initial date are in excess of 5% implying a total average price effect between 12% and 15% from implementing a buy-back plan. We conjecture that the German regulatory environment is the main reason why market variations to buy-back announcements are much stronger in Germany than in other countries and conclude that initial statements by managers to seek shareholders? approval for a buy-back plan should also be subject to legal ad-hoc disclosure requirements.
Keywords: 330; Aktienrückkauf; Ankündigungseffekt; Börsenkurs; Kapitalertrag; Publizitätspflicht; Schätzung; Deutschland